Impact of routine manual aspiration thrombectomy on outcomes of patients undergoing primary percutaneous coronary intervention for acute myocardial infarction: A meta-analysis. (1st February 2016) - Barkagan, Michael; Steinvil, Arie; Berchenko, Yakir; Finkelstein, Ariel; Keren, Gad; Banai, Shmuel; Halkin, Amir
Abstract: Background: The efficacy and safety of thrombectomy as an adjunct to primary percutaneous intervention (PCI) in the management of acute myocardial infarction (AMI) are debated. We performed a meta-analysis of randomized trials comparing primary PCI performed with versus without routine aspiration thrombectomy (AT). Methods: A meta-analysis of randomized AT trials reporting clinical outcomes was done in accordance with the PRISMA guidelines. Trials reporting only non-clinical endpoints and those of technologies other than manual devices were excluded. The primary endpoint of this meta-analysis was mortality (either all-cause or cardiovascular). Secondary endpoints were reinfarction, stent thrombosis, and stroke. Results: Seventeen randomized trials, involving 20, 853 patients were included. Weighted mean follow-up was 9.3 ± 3.3 months. The rates of all-cause mortality (reported in 14 trials, n = 10, 430) and cardiovascular mortality (reported in 6 trials, n = 11, 810) did not differ significantly between patients treated with or without AT (4.6% vs. 5.3%, RR = 0.88 [95%CI = 0.75–1.04]; and, 3.0% vs. 3.7%, RR = 0.83 [95%CI = 0.68–1.01]; respectively). The rates of reinfarction and stent thrombosis were also similar in patients treated with versus those treated without AT (2.1% vs. 2.2%; RR = 0.96 [95%CI = 0.80–1.15]; and, 1.2% vs. 1.4%; RR = 0.84 [95%CI = 0.65–1.07], respectively). However, stroke rates were increased with AT (0.84% vs. 0.52%, RR = 1.56 [95%CI = 1.09–2.25]). Conclusions: Routine AT as an adjunct to primary PCI does not reduce the rates of death, reinfarction, or stent thrombosis, but is associated with increased stroke risk.